Hubungan Komunikasi Interpersonal Dosen Pembimbing Mahasiswa Terhadap Tekanan Psikologis Dalam Menyusun Skripsi - Waode Rhevi Silviani; Hastuti Hastuti; Wa Nur Fida (Jurnal Ilmiah Komunikasi (JIKOM) STIKOM IMA, 2023)
In studying in higher education to get a bachelor's degree that students want to achieve, they are required to make an ilimiah or Thesis paper. Students who compile the thesis experience stress because they are unable to overcome the challenges they face. It is caused by internal causes and external causes, internal causes there is a level of ability and level of student intelligence. Then the insistence of the family, the demands of the campus, and financial problems are the external causes. Therefore, students need a supervisor to complete the thesis, a form of solving the problem, namely good communication between students and supervisors so that the relationship between students and good thesis supervisors can facilitate student tasks in compiling a thesis. Based on the type of data obtained in this study, the authors used quantitative methods using descriptive research methods to describe the results of the research conducted. In this study the authors used questionnaires as a tool to collect data. Then the data obtained were analyzed using validity tests, reability tests, normality tests, heteroskedasity tests, simple linear regression analysis, t (partial) tests and determinant tests with the help of SPSS Application version 22. With a total population of 100 students and a sample of 50 respondents. From the results of the analysis carried out by researchers, it can be concluded that there is an influence of Communication Relations Interpersonal Student Supervisor to Psychological Pressure in Compiling a Thesis, this means that H0 is rejected and H1 is accepted